Atorvastatin Has a Dose‐Dependent Beneficial Effect on Kidney Function and Associated Cardiovascular Outcomes: Post Hoc Analysis of 6 Double‐Blind Randomized Controlled Trials. Issue 9 (7th May 2019) - Vogt, Liffert; Bangalore, Sripal; Fayyad, Rana; Melamed, Shari; Hovingh, G. Kees; DeMicco, David A.; Waters, David D.
Abstract : Background: Kidney function decreases during the lifetime, and this decline is a powerful predictor of both kidney and cardiovascular outcomes. Statins lower cardiovascular risk, which may relate to beneficial effects on kidney function. We studied whether atorvastatin influences kidney function decline and assessed the association between individual kidney function slopes and cardiovascular outcome. Methods and Results: Data were collected from 6 large atorvastatin cardiovascular outcome trials conducted in patients not selected for having kidney disease. Slopes of serum creatinine reciprocals representing measures of kidney function change ([mg/dL] −1 /y), were analyzed in 30 621 patients. Based on treatment arms, patients were categorized into 3 groups: placebo (n=10 057), atorvastatin 10 mg daily (n=12 763), and 80 mg daily (n=7801). To assess slopes, mixed‐model analyses were performed for each treatment separately, including time in years and adjustment for study. These slopes displayed linear improvement over time in all 3 groups. Slope estimates for patients randomized to placebo or atorvastatin 10 mg and 80 mg were 0.009 (0.0008), 0.011 (0.0006), and 0.014 (0.0006) (mg/dL) −1 /y, respectively. A head‐to‐head comparison of atorvastatin 10 and 80 mg based on data from 1 study (TNT [Treating to New Targets]; n=10 001) showed a statistically significant difference in slope between the 2 doses ( P =0.0009). From a Cox proportional hazards model using slope as a predictor, a significant ( P <0.0001) negative association between kidney function and cardiovascular outcomes was found. Conclusions: In patients at risk of or with cardiovascular disease, atorvastatin improved kidney function over time in a dose‐dependent manner. In the 3 treatment groups, kidney function improvement was strongly associated with lower cardiovascular risk. Clinical Trial Registration: URL: http://www.clinicaltrials.gov . Unique identifiers: NCT00327418; NCT00147602; NCT00327691.